Day labor, informality and vulnerability in South Africa and the United States. Issue 6 (7th September 2015) - John Burgess and Professor Julia Connell, Professor; Theodore, Nik; Blaauw, Derick; Schenck, Catherina; Valenzuela Jr., Abel; Schoeman, Christie; Meléndez, Edwin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to compare conditions in informal day-labor markets in South Africa and the USA to better understand the nature of worker vulnerabilities in this market, as well as the economic conditions that have contributed to the growth of day labor. The conclusion considers interventions that are underway in the two countries to improve conditions in day-labor markets. Design/methodology/approach – The paper is based on national surveys of day laborers in South Africa and the USA. A random sample of day laborers seeking work at informal hiring sites was undertaken in each country. The paper presents key findings, compares conditions in South Africa and the USA, and analyzes the relationship between economic change, labor-market dynamics, and worker vulnerability. Findings – Day-labor work is characterized by low pay, hazardous conditions on the job, and tremendous income insecurity. The day-labor markets in South Africa and the USA perform somewhat different functions within regional economies. Within South Africa, day labor can be regarded as a survival strategy. The growth of day labor in South Africa over the past decade is a manifestation of a formal labor market that is incapable of absorbing the structurally unemployed. Here, day labor is the employment of last resort, allowing workers to subsist on the fringes of the mainstream economy, but offering few pathways into the formal sector. In the USA, the day labor workforce is a largely undocumented-immigrant workforce. Workers seek work at informal hiring sites, maintaining a tenuous hold on jobs in the construction industry. There is evidence of some mobility into more stable and better paying employment. Practical implications – This paper documents the need for policies and programs to increase employment opportunities for day laborers and to better enforce labor standards in the informal economy. Originality/value – This paper summarizes findings from the only two national surveys of day laborers that have been conducted, and it compares for the first time the dynamic within growing day-labor markets in a developed- and emerging-market context.